Beta-Actin Is Involved in Modulating Erythropoiesis during Development by Fine-Tuning Gata2 Expression Levels. - Davina Tondeleir; Benjamin Drogat; Karolina Slowicka; Karima Bakkali; Sonia Bartunkova; Steven Goossens; Jody J Haigh; Christophe Ampe (PLoS ONE, 2013)
The functions of actin family members during development are poorly understood. To investigate the role of beta-actin in mammalian development, a beta-actin knockout mouse model was used. Homozygous beta-actin knockout mice are lethal at embryonic day (E)10.5. At E10.25 beta-actin knockout embryos are growth retarded and display a pale yolk sac and embryo proper that is suggestive of altered erythropoiesis. Here we report that lack of beta-actin resulted in a block of primitive and definitive hematopoietic development. Reduced levels of Gata2, were associated to this phenotype. Consistently, ChIP analysis revealed multiple binding sites for beta-actin in the Gata2 promoter. Gata2 mRNA levels were almost completely rescued by expression of an erythroid lineage restricted ROSA26-promotor based GATA2 transgene. As a result, erythroid differentiation was restored and the knockout embryos showed significant improvement in yolk sac and embryo vascularization. These results provide new molecular insights for a novel function of beta-actin in erythropoiesis by modulating the expression levels of Gata2 in vivo.